Media and Terrorism: Interrogating the Role of News Coverage of Boko Haram Insurgency in Nigeria - Ibrahim Abdulkadir (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2025)
The relationship between media and terrorism has long been debated, with scholars emphasising that while the media provides essential information about terrorist activities, it simultaneously offers publicity that sustains terror networks. This study interrogates the role of Nigerian news coverage in shaping public understanding of the Boko Haram insurgency. Drawing on agenda-setting theory, the paper examines how the media have represented Boko Haram’s activities, motivations, and impacts on society. It investigates whether such portrayals contribute to public fear, legitimize government counter-terrorism measures, or inadvertently amplify the insurgents’ propaganda. Using the secondary data from the existing literature, the study highlights the complexities of reporting terrorism in a conflict-ridden environment. The findings reveal patterns of sensationalism, the dominance of government perspectives, and limited contextualization of the socio-economic drivers of terrorism. This study has demonstrated that the relationship between media and terrorism, particularly in the Nigerian context, is both complex and consequential. News coverage of the Boko Haram insurgency reveals not only the challenges of reporting in a volatile security environment but also the power of the media in framing public perceptions of terrorism. The paper concludes that by fostering a more responsible media practice, the Nigerian press can play a transformative role in countering extremist ideologies, promoting national cohesion, and contributing to long-term peacebuilding efforts in regions affected by terrorism.